Diversity, Equity, and Inclusion (DEI) in Contemporary Human Resource Management Practices - Bakti Kurniawan; Ifah Rofiqoh (Maneggio, 2026)
The development of modern organizations is characterized by increasing workforce diversity and social demands for fairness and inclusivity in the workplace. These conditions have driven a paradigm shift in human resource management from a homogenous approach to a Diversity, Equity, and Inclusion (DEI) framework. This study aims to analyze the conceptual development of DEI, its implementation in contemporary human resource management practices, and its implications for organizational performance and sustainability. The research approach uses a qualitative method through a literature review by reviewing scientific journal articles, academic books, and reports from reputable organizations relevant to the topics of DEI and HRM. Data analysis was conducted using thematic analysis techniques to identify conceptual patterns, key practices, and challenges in DEI implementation. The results of the study indicate that diversity, equity, and inclusion are interrelated and inseparable dimensions in modern human resource management. DEI implementation has been shown to contribute to increased employee engagement, innovation, and organizational legitimacy and reputation. However, DEI implementation still faces obstacles in the form of cultural resistance, implicit bias, and symbolic tendencies in organizational policies. This study emphasizes the importance of substantive DEI integration into HRM strategies to support long-term organizational sustainability